CHANGING COMPETENCIES OF LEADERS: WHAT THE NEW GENERATION EXPECTS FROM THEIR LEADERS - Cavusoglu, Kagan (E-Journal VFU, 2025)
With changing technology and Generation Z joining the work life, the perception of leadership has transformed. Leadership practices aligned with the expectations and needs of the new generation should now be discussed in the literature. This conceptual qualitative review investigates the competencies leaders should have in line with the expectations of Generation Z. Studies in the literature published between 2000 and 2025, based on the concepts of leadership, organizational behavior, and generation, were systematically analyzed. As a result of the thematic synthesis, five competency axes were determined in contemporary leadership approaches that align with the expectations of Generation Z, which are empathy, flexibility, participation, psychological safety, and ethical transparency. These five competencies indicate that leadership practices have shifted from control in traditional approaches to a connection-centered paradigm. This transformation tells us that concepts like meaning, trust, and value have now become the fundamental components of organizational commitment and sustainability. This study introduces the concept of "Adjusted Leadership," which argues that leadership is a process that constantly adjusts to context, culture, and generational dynamics, adapting to both psychological and cognitive transformation, rather than a standard set of competencies. This approach prioritizes the changing emotional states and needs of followers and provides an environment of psychological safety. Future studies will empirically test this approach across cultural and sectoral contexts and contribute to the development of a leadership theory centered on human experience.